Corticimarasmius bambusicola gen. et sp. nov. (Agaricales, Basidiomycota) from southern China - Zhang, Yu-Peng; Ye, Jing; Li, Yue; Huang, Man-Rong; Yang, Ning; He, Si-Yi; He, Shuang-Hui (Phytotaxa, 2025)
Agaricales, the largest and most diverse order of mushroom-forming Basidiomycota, also includes numerous species with corticioid, clavarioid, or gastroid basidiomata. In the present study, an unknown lineage, described as Corticimarasmius bambusicola gen. et sp. nov., is found in the ITS-nrLSU phylogenetic tree of the order. The species belongs to the corticioid fungi with strictly resupinate, effused, thin, membranaceous basidiomata, growing on bamboos in Yunnan and Hubei Province in central and southwestern China. It is characterized by smooth to pulverulent hymenophores, a dimitic hyphal system with clamped generative hyphae and skeletal-like hyphae, two kinds of differently shaped gloeocystidia, and subfusiform to subcylindrical basidiospores negative in Cotton Blue and Melzer’s reagents. Descriptions and illustrations are provided for the new taxa.